The Implementasi Media Pop Up pada Pembelajaran Pendidikan Pancasila tentang Simbol Keberagaman Agama di Kelas 2 SD dengan Pendekatan Culturally Responsive Teaching - Fillah, Alifia Hasna Azzah; Barokah Isdaryanti; Alifia Edria Adikasari; Anindhyta Putri Pradipta (Qalam : Jurnal Ilmu Kependidikan, 2025)
Pancasila Education (PP) learning in elementary schools needs to present engaging and contextual media so that students can better understand the values of diversity. This study examines the practice of using pop-up media that displays symbols of religious diversity in the city of Semarang, implemented in a Grade 2 class at Labschool UNNES, using the Culturally Responsive Teaching (CRT) model. The three-dimensional pop-up media is expected to enhance student engagement and foster a sense of wonder, while also introducing them to local culture and religious diversity in their surroundings. This research employed a descriptive study method through direct observation during the learning process. The findings indicate that the use of pop-up media effectively increases student participation in discussions and their understanding of tolerance values. It is recommended that teachers develop culturally and contextually relevant media to enrich students’ learning experiences.